Sosialisasi Dampak Penggunaan Merkuri pada Pekerja Tambang Rakyat di Desa Buladu, Kecamatan Sumalata Timur, Kabupaten Gorontalo Utara - Sukamto, Kostiawan; Lukum, Astin; Pikoli, Masrid; Kilo, Akram La (Damhil: Jurnal Pengabdian kepada Masyarakat, 2024)
The awareness campaign on the impact of mercury use among artisanal miners in Buladu Village, East Sumalata District, North Gorontalo Regency, aimed to enhance knowledge about the dangers of mercury and introduce safer alternative mining methods. The event saw enthusiastic participation from 75 attendees, including miners, their families, and community representatives. The activities included pre-tests and post-tests, which showed a significant increase in participants' knowledge, with average scores rising from 45% to 85%. Interactive discussions and practical workshops revealed a high interest in understanding and adopting mercury-free mining methods. While some participants did not fully grasp the material, the majority rated the relevance of the information and the quality of the speakers as very good. Overall satisfaction was high, with 85% of participants feeling satisfied or very satisfied, and 80% expressing interest in further training. The survey also indicated a need for additional support, such as training, technical assistance, and ongoing education. Regular monitoring and the formation of working groups or cooperatives among miners are recommended to facilitate the implementation of alternative technologies and knowledge sharing. With appropriate follow-up actions, this initiative is expected to have a sustainable positive impact on the health and well-being of miners and the environmental preservation in Buladu Village.